A pilot genome-scale profiling of DNA methylation in sporadic pituitary macroadenomas: association with tumor invasion and histopathological subtype. - Chao Ling; Matthew Pease; Lingling Shi; Vasu Punj; Mark S Shiroishi; Deborah Commins; Daniel J Weisenberger; Kai Wang; Gabriel Zada (PLoS ONE)
Pituitary adenomas (PAs) are neoplasms that may cause a variety of neurological and endocrine effects. Although known causal contributors include heredity, hormonal influence and somatic mutations, the pathophysiologic mechanisms driving tumorigenesis and invasion of sporadic PAs remain unknown. We hypothesized that alterations in DNA methylation are associated with PA invasion and histopathology subtype, and that genome-scale methylation analysis may complement current classification methods for sporadic PAs. Twenty-four surgically-resected sporadic PAs with varying histopathological subtypes were assigned dichotomized Knosp invasion scores and examined using genome-wide DNA methylation profiling and RNA sequencing. PA samples clustered into subgroups according to functional status. Compared with hormonally-active PAs, nonfunctional PAs exhibited global DNA hypermethylation (mean beta-value 0.47 versus 0.42, P = 0.005); the most significant site of differential DNA methylation was within the promoter region of the potassium voltage-gated channel KCNAB2 (FDR = 5.11×10-10). Pathway analysis of promoter-associated CpGs showed that nonfunctional PAs are potentially associated with the ion-channel activity signal pathway. DNA hypermethylation tended to be negatively correlated with gene expression. DNA methylation analysis may be used to identify candidate genes involved in PA function and may potentially complement current standard immunostaining classification in sporadic PAs. DNA hypermethylation of KCNAB2 and downstream ion-channel activity signal pathways may contribute to the endocrine-inactive status of nonfunctional PAs.